2009
DOI: 10.1021/la900066z
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Biosensor Based on Nanocomposite Films of CdTe Quantum Dots and Glucose Oxidase

Abstract: A blood glucose sensor has been developed based on the multilayer films of CdTe semiconductor quantum dots (QDs) and glucose oxidase (GOD) by using the layer-by-layer assembly technique. When the composite films were contacted with glucose solution, the photoluminescence of QDs in the films was quickly quenched because the enzyme-catalyzed reaction product (H2O2) of GOD and glucose gave rise to the formation of surface defects on QDs. The quenching rate was a function of the concentration of glucose. The linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 173 publications
(93 citation statements)
references
References 62 publications
1
91
1
Order By: Relevance
“…In the similar way, HRP and GOx were proved to be successfully immobilized at PDDA/HRP/Au-BC/GCE and PDDA/ GOx/Au-BC/GCE. The R et of PDDA/GOx-HRP/Au-BC/ GCE was much smaller than that of PDDA/GOx-HRP/ GCE (1027 W), indicating Au-BC nanocomposite had good conductivity and could make the electron transfer of [Fe(CN) 6 ] 3À/4À easily.…”
Section: Electrochemical Characterizationsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the similar way, HRP and GOx were proved to be successfully immobilized at PDDA/HRP/Au-BC/GCE and PDDA/ GOx/Au-BC/GCE. The R et of PDDA/GOx-HRP/Au-BC/ GCE was much smaller than that of PDDA/GOx-HRP/ GCE (1027 W), indicating Au-BC nanocomposite had good conductivity and could make the electron transfer of [Fe(CN) 6 ] 3À/4À easily.…”
Section: Electrochemical Characterizationsmentioning
confidence: 92%
“…Figure 2 exhibited the Nyquist plot of EIS at the bare and the modified GCEs, which were obtained in 4.0 mM [Fe(CN) 6 ] 3À/4À solution with the frequencies from 100 kHz to 0.1 Hz. Significant differences in the impedance spectra were observed.…”
Section: Electrochemical Characterizationsmentioning
confidence: 99%
“…Although numerous established strategies have been successfully employed to construct new nanocomposite biosensors, several limitations, such as time and cost, diffi culty of large -scale production, and absence of universality, inevitably hinder the practical applications of such methods [15,43] . Since Decher [118] pioneeringly introduced an alternative way to develop a new generation of nanocomposite biosensor based on the alternative deposition of oppositely charged species on the substrates by using the electrostatic layer -by -layer self -assembly technique, membranes designed layer -bylayer are expected to contribute in that sense due to their simplicity, economy, universality, and environmentally friendly properties [15,119,120] . In most cases, membranes are in the form of permselective planar fi lms (organosilane, polyurethane, cellulose acetate, etc.)…”
Section: Polymer Membranesmentioning
confidence: 99%
“…Faure et al [43] also reported generating amperometric biosensors by a new enzyme immobilization process and investigated the analytical properties of polypyrrole biosensors made with free or encapsulated GOx. Recently, Tang et al [15] fabricated a blood glucose sensor based on multilayer fi lms of CdTe semiconductor quantum dot s ( QD s) and GOx by using the layer -by -layer assembly technique, as shown in Figure 5.3 .…”
Section: Polymer Membranesmentioning
confidence: 99%
See 1 more Smart Citation